(untitled) (Third Sector Social Economic Review, 2026)
The purpose of this study is to examine the relationship between toxic leadership and organizational silence within a reciprocal and cyclical framework, going beyond a one-directional effect perspective. The study tests both the effects of toxic leadership dimensions (abusiveness, self-promotion, narcissism, unpredictability, and authoritarianism) on types of organizational silence (acquiescent, defensive, and prosocial silence) and how these silence types, in turn, influence toxic leadership behaviors. Data were collected through a survey from 567 employees working in different sectors in the province of Kırklareli, Turkey. Schmidt’s (2008) Toxic Leadership Scale and Van Dyne et al.’s (2003) Organizational Silence Scale were utilized. The hypotheses were tested using multiple regression analyses. The findings indicate that abusiveness and self-promotion increase acquiescent silence, whereas acquiescent and defensive silence strengthen narcissistic and unpredictable leadership behaviors. In contrast, prosocial silence was found to weaken certain dimensions of toxic leadership. Overall, the study demonstrates that the relationship between toxic leadership and organizational silence is not linear but dynamic and based on reciprocal interactions, and it proposes a comprehensive model to explain this relationship in the organizational behavior literature.